Archaeological studies of shell-remains at Punangatu (Futuna island/Vanuatu) – How can we identify and classify shellfish to understand their historical use? - Lucas Sarvanu; Matthias Kowasch (Pacific Geographies, 2020)
This article, based on the master’s thesis of the first author, aims to identify and classify by species different shellfish collected in a Vanuatu archaeological site. We want to analyse how these shells have been modified and utilized to produce furniture and artefacts. The results show that the Punangatu shell assemblage is dominated by Gastropods, in particular by the families of Turbnidae and Trochidae, which were easy and accessible to exploit. The two families are still consumed today. But the share of shellfish and the importance of fishing during the island’s initial settlement and over time remains unclear. It would be necessary in the future to study other sites of the island to better understand the societal role of marine resources.